Alister E. McGrath and evangelical theology a dynamic engagement - Chung, Sung Wook, 1966- (Carlisle, UK Paternoster, 2003)
Includes bibliographical references.
Produced in celebration of Alister McGrath's 50th birthday
Keywords: McGrath, Alister Edgar, -- 1953-; Evangelicalism -- theology